Low-thermal-conductivity Pb-Bi-S-based ternary compound and preparation method thereof

By compositing InSb into the PbBi2S4 matrix, the electrical transport performance was optimized and the lattice thermal conductivity was reduced, solving the problems of high cost and poor performance of Te-based thermoelectric materials, and preparing a low thermal conductivity Pb-Bi-S-based ternary compound suitable for large-scale applications.

CN120887724APending Publication Date: 2025-11-04SICHUAN SAIPER MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510974831.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing Te-based thermoelectric materials are expensive and have poor electrical transport properties, which limits their large-scale application.

Method used

The Pb-Bi-S based ternary compound PbBi2S4-x%InSb was used to optimize electrical transport properties and reduce lattice thermal conductivity by incorporating InSb into the PbBi2S4 matrix. The preparation methods include melt reaction and vacuum hot pressing sintering.

Benefits of technology

A low-cost, high thermoelectric performance Pb-Bi-S-based ternary compound was achieved, with lattice thermal conductivity decreasing to 0.56-0.30 W m-1 K-1 within the range of 300-773 K and a maximum ZT value of 0.72, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120887724A_ABST
    Figure CN120887724A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy materials, and relates to a thermoelectric material, in particular to a low-thermal-conductivity Pb-Bi-S-based ternary compound PbBi2S4-x% InSb and a performance optimization method thereof. The S-based ternary compound disclosed by the invention does not contain Te and shows relatively low manufacturing cost; the preparation period is only 30 hours, the process is simple, the repeatability is high, and large-scale manufacturing can be realized; the lattice thermal conductivity of the prepared Pb-Bi-S-based ternary compound PbBi2S4-x% InSb in a temperature range of 300 to 773 K can be as low as 0.56 to 0.30 W m <-1 > K <-1 >; the maximum thermoelectric figure of merit of the S-based ternary compound can be optimized to 0.72; the material has performance and cost advantages, and is a novel thermoelectric candidate material with low thermal conductivity and great potential.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of energy materials, and relates to a thermoelectric material, in particular to a low-thermal-conductivity Pb-Bi-S-based ternary compound and a preparation method thereof. BACKGROUND

[0002] Thermoelectric power generation technology can effectively recover waste heat, improve energy conversion efficiency, help reduce dependence on fossil fuels, and significantly reduce carbon emissions. In addition, thermoelectric refrigeration technology can achieve precise temperature control and has wide application prospects in the fields of biological engineering, medical health, modern industry, national defense and military, scientific research, electronic technology, daily life, etc. Therefore, developing high-performance thermoelectric materials is more conducive to promoting society to move towards a green, environmentally friendly and efficient lifestyle.

[0003] Commercial bismuth telluride (Bi2Te3) thermoelectric materials and traditional high-performance PbTe thermoelectric materials both contain scarce and expensive Te elements, which is not conducive to large-scale production and application of this series of thermoelectric materials. The S element has a high crustal abundance and a low price compared to the Te element, so that the S-based thermoelectric material has a lower manufacturing cost. Compared with binary compounds, ternary compounds generally have lower intrinsic lattice thermal conductivity due to their more complex crystal structure. Therefore, S-based ternary compounds have the advantages of low cost and low lattice thermal conductivity. Among them, Pb-Bi-S ternary compounds have attracted widespread attention due to their lower intrinsic lattice thermal conductivity. However, the strong coupling between electrons and phonons in thermoelectric materials makes Pb-Bi-S ternary compounds have poor electrical transport performance. Therefore, while maintaining the advantage of low thermal conductivity, improving the electrical transport performance, and ultimately obtaining a low-cost, high-thermoelectric-performance Pb-Bi-S-based ternary compound, it is more conducive to promoting the wide application of thermoelectric technology. SUMMARY

[0004] In view of the above problems, in order to solve the problem of high cost of traditional binary Te-based thermoelectric materials, the application provides a low-thermal-conductivity Pb-Bi-S-based ternary compound PbBi2S4-x%InSb. The PbBi2S4 ternary compound substrate prepared therefrom exhibits extremely low lattice thermal conductivity in the full temperature range (300-773 K), 0.57-0.41 W m -1 K -1 ; the lattice thermal conductivity of the PbBi2S4-2.5%InSb ternary compound obtained by compounding InSb in the PbBi2S4 ternary compound is further reduced in the full temperature range, 0.56-0.30 W m -1 K -1Meanwhile, the overall electrical performance of PbBi2S4 is greatly improved, and the thermoelectric performance of the ternary compound PbBi2S4 is significantly optimized. Obviously, the Pb-Bi-S-based ternary compound has performance and cost advantages, and is a new type of potential thermoelectric candidate material.

[0005] The specific technical solutions of the present application are as follows: In one aspect, a low-thermal-conductivity Pb-Bi-S-based ternary compound is characterized in that the chemical formula of the low-thermal-conductivity Pb-Bi-S-based ternary compound is PbBi2S4-x%InSb, 0.5≤x≤4.0, which has low cost and excellent thermoelectric performance; wherein the Pb-Bi-S-based ternary compound substrate PbBi2S4 is prepared by melting Pb, Bi and S elements in a molar ratio of 1:2:4, and has a low intrinsic lattice thermal conductivity; InSb is compounded in the PbBi2S4 substrate to further reduce the lattice thermal conductivity of the substrate, forming the low-thermal-conductivity Pb-Bi-S-based ternary compound PbBi2S4-x%InSb.

[0006] Compared with binary compounds, ternary compounds generally have more complex crystal structures, and thus have lower intrinsic lattice thermal conductivities. S-based ternary compounds have low cost and low intrinsic lattice thermal conductivity. Among them, PbBi2S4, as one of the Pb-Bi-S ternary compound series, has a lower lattice thermal conductivity among S-based ternary compounds.

[0007] Generally, high-performance thermoelectric materials need to have both high electrical transport performance and low thermal conductivity. Therefore, we subsequently compounded InSb with excellent electrical transport performance in the PbBi2S4 ternary compound substrate to further optimize its electrical transport performance. InSb not only effectively optimizes the carrier concentration of the substrate, but also provides a fast carrier transport channel to enhance the electrical transport performance. Furthermore, InSb can further enhance phonon scattering, further reducing the lattice thermal conductivity of the PbBi2S4 substrate, thereby achieving synergistic optimization of the thermoelectric performance of the Pb-Bi-S-based ternary compound.

[0008] Preferably, in the PbBi2S4 substrate of the Pb-Bi-S-based ternary compound, the molar ratio of Pb, Bi and S elements is 1:2:4.

[0009] Preferably, in the low-thermal-conductivity Pb-Bi-S-based ternary compound, the compounding amount of InSb is 0.5≤x≤4.0.

[0010] Preferably, the low-thermal-conductivity Pb-Bi-S-based ternary compound is PbBi2S4-2.5%InSb.

[0011] In another aspect, the present application provides a method for preparing the low thermal conductivity Pb-Bi-S-based ternary compound, comprising the following steps: Step 1, the present application first obtains the Pb-Bi-S-based ternary compound precursor mixture according to the molar ratio of 1:2:4 of Pb, Bi and S. Then, the raw materials are weighed according to the atomic stoichiometric ratio of PbBi2S4-x%InSb to obtain the low thermal conductivity Pb-Bi-S-based ternary compound mixture.

[0012] Step 2, the mixture prepared in step 1 is placed in a vacuum quartz tube, sealed by flame, then subjected to melting reaction at a high temperature environment of 1100±50 ℃ for at least 6 h, and finally cooled with the furnace to obtain Pb-Bi-S-based ternary compound ingot.

[0013] Step 3, the Pb-Bi-S-based ternary compound ingot is ground into powder, which is loaded into a mold for vacuum hot pressing sintering treatment to obtain a low thermal conductivity Pb-Bi-S-based ternary compound disc-shaped sample.

[0014] Preferably, in step 1, the elemental mass purity of Pb, S and Sb raw materials is greater than 99.999%, and the purity of In and Bi raw materials is greater than 99.99%.

[0015] Preferably, in step 1, the vacuum degree in the vacuum quartz tube is less than 10 -3 Pa.

[0016] Preferably, in step 2, the temperature control program of the high temperature environment is: increasing to 1100±50 ℃ within 15-30 h, and maintaining for at least 6 h.

[0017] Preferably, in step 3, the specific process of vacuum hot pressing sintering treatment is: maintaining at a pressure of 40-50 MPa and a temperature of 500±50 ℃ for at least 5 minutes.

[0018] The only commercial thermoelectric material Bi2Te3 alloy and the traditional high-performance thermoelectric material PbTe both have high manufacturing cost; and the binary compounds that can be used for thermoelectric application have been exhausted. The low thermal conductivity Pb-Bi-S-based ternary compound provided by the present application has the beneficial effects of: 1) S-based compound has low manufacturing cost and high economic benefit, which is conducive to the wide application of thermoelectric materials; 2) the complex crystal structure of ternary compound endows it with low intrinsic lattice thermal conductivity, which is conducive to obtaining high thermoelectric performance.

[0019] In summary, the application improves the electrical transport performance of the PbBi2S4-based ternary compound by compounding InSb with high electrical transport performance in the low-cost S-based ternary compound PbBi2S4, further reduces the lattice thermal conductivity, and improves the electrical transport performance of the PbBi2S4-based ternary compound, thereby significantly improving the thermoelectric figure of merit. The Pb-Bi-S-based ternary compound has the advantages of low raw material cost and low manufacturing cost. Compared with Te-based thermoelectric materials, the low-thermal-conductivity S-based ternary compound PbBi2S4-x%InSb in the application does not contain the expensive and scarce element Te, which can significantly reduce the cost of raw materials. The low-thermal-conductivity Pb-Bi-S-based ternary compound PbBi2S4-x%InSb in the application is a polycrystalline thermoelectric material, which has the advantages of short preparation period, simple preparation process, good repeatability, and is conducive to large-scale production. The Pb-Bi-S-based ternary compound prepared in the application has extremely low lattice thermal conductivity. The lattice thermal conductivity of the PbBi2S4-based ternary compound is 0.57-0.41 W m -1 K -1 in a wide temperature range of 300-773 K. After compounding InSb, the lattice thermal conductivity of PbBi2S4-2.5%InSb is as low as 0.56-0.30 W m -1 K -1 in a wide temperature range of 300-773 K. The PbBi2S4-based ternary compound has excellent thermoelectric performance. The inherent low thermal conductivity of the PbBi2S4-based ternary compound provides an opportunity to improve the electrical performance. After compounding InSb to optimize the thermoelectric performance, the maximum ZT value can reach 0.72. Moreover, the compounding strategy significantly improves the feasibility of the thermoelectric performance of the PbBi2S4-based ternary compound. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The figure is a comparison chart of the crust abundance and price of Te and S elements, and the lattice thermal conductivity of the PbBi2S4-based ternary compound and other S-based ternary compounds. The examples are only used to explain and describe the application.

[0021] Figure 2 The figure is a structural schematic diagram of the high-temperature muffle furnace and the vacuum hot-pressing furnace used in the examples and the PbBi2S4-based ternary compound.

[0022] Figure 3 The figure is a phase analysis, crystal structure of the PbBi2S4-based ternary compound, and phase analysis of the examples.

[0023] Figure 4 The figure is a thermoelectric performance measurement chart of the examples and the PbBi2S4-based ternary compound.

[0024] Figure 5The lattice thermal conductivities of the optimal composition PbBi2S4-2.5%InSb and the PbBi2S4 matrix at different temperatures are compared. ZT DETAILED DESCRIPTION

[0025] The technical solutions and advantages of the present application will be further described in detail below in combination with the drawings and examples, but the content of the present application is not limited to the following examples.

[0026] Figure 1 The crust abundance and price comparison chart of Te and S elements, and the lattice thermal conductivity of the PbBi2S4 matrix and other S-based ternary compounds are shown in (a) and (b). As can be seen from (a), compared with Te element, S element has more abundant reserves and lower price, so S-based thermoelectric materials have a significant cost advantage compared with Te-based thermoelectric materials. As can be seen from (b), among the reported S-based ternary compounds, PbBi2S4, as one of the Pb-Bi-S ternary compound series, has a lower lattice thermal conductivity. Therefore, the S-based ternary compound PbBi2S4 is a potential thermoelectric material with low cost and low intrinsic lattice thermal conductivity. EMBODIMENT

[0027] A preparation method of a low-thermal-conductivity Pb-Bi-S-based ternary compound, comprising the following steps: Step 1: Pb blocks, S powder, Sb blocks and In blocks and Bi blocks with a purity of more than 99.999% are weighed according to the atomic stoichiometric ratio of PbBi2S4-x%InSb to obtain a mixture. The content of x is taken as 2.0, 2.5 and 3.0 respectively for corresponding examples 1-3. In addition, in order to fully demonstrate the advantages of examples 1-3, PbBi2S4 is added as a comparison.

[0028] Step 2: The mixture obtained in step 1 is placed in a flat-bottomed quartz tube with an inner diameter of 12 mm, and then the quartz tube is subjected to vacuum treatment with a vacuum degree of less than 10 -3 Pa, and then the quartz tube is sealed by flame and placed in a high-temperature muffle furnace for melting reaction.

[0029] The temperature control program of the high-temperature muffle furnace is as follows: 20 h for temperature rising to 1100 ℃, and 10 h for temperature holding, and then the furnace is cooled to room temperature to obtain Pb-Bi-S-based ternary compounds and PbBi2S4 matrix materials.

[0030] ​Step 3, the Pb-Bi-S-based ternary compound obtained in Step 2 and the PbBi2S4-based matrix material are ground into powder by using an agate mortar, and about 3 g of powder is reserved for corresponding phase analysis, and the rest is loaded into a graphite mold (diameter of 15 mm) padded with carbon paper, and the graphite mold is placed in a vacuum hot pressing furnace for sintering and forming.

[0031] The pressure and temperature control program of the vacuum hot pressing furnace is as follows: pressure of 50 MPa (883 Kg), pressure maintaining time of 50 min. First, the pressure is increased to 883 Kg (50 MPa), and after 2 min, the temperature program is started, and the temperature is increased to 500 ℃, and the pressure is maintained at 883 Kg and the temperature is maintained at 500 ℃ for 5 min. After the program is completed, the sample is cooled to room temperature with the furnace, and a dense disc-shaped bulk sample is obtained, with a diameter of 15 mm and a height of 10-13 mm, and the height is determined by the amount of powder loaded.

[0032] Step 4, the dense disc-shaped bulk sample obtained in Step 3 is cut into a size required for thermoelectric testing using a low-speed cutting machine, and then the sample for electrical and thermal performance testing is polished using sandpaper. In this embodiment, the sample size required for electrical performance testing is about 3 mm*3 mm*10 mm cuboid, and the sample size required for thermal performance testing is about 6 mm*6 mm*1.2 mm square sheet.

[0033] Figure 2 The structural schematic diagram of the high-temperature muffle furnace and the vacuum hot pressing furnace used for the examples and the PbBi2S4-based matrix. Among them, (a) is the structural schematic diagram of the high-temperature muffle furnace, and the mixed material is sealed in a flat-bottomed quartz tube, the quartz tube is inserted into the refractory brick, and the melting reaction is carried out under the temperature control program. (b) is the structural schematic diagram of the vacuum hot pressing furnace, and the powder sample is placed in a graphite mold, and the hot pressing sintering is carried out in a vacuum environment.

[0034] The phase analysis of Examples 1-3 and the PbBi2S4-based matrix is carried out using an X-ray diffractometer, and the XRD results of the PbBi2S4-based matrix are analyzed by refinement, and the results are shown in Figure 3 .

[0035] Figure 3 The phase analysis, crystal structure of the PbBi2S4-based matrix and the phase analysis of the examples. Among them, (a) is the phase analysis of the PbBi2S4-based matrix, (b) is the crystal structure of the PbBi2S4-based matrix, and (c) is the phase analysis of the PbBi2S4-based matrix and the examples. As can be seen from the figure, the PbBi2S4 ternary compound is successfully prepared by the preparation method provided by the present application, and no second phase is found after the InSb is compounded, which ensures the consistency of the main phase after the compounding.

[0036] Through the above Figure 1(b), it is known that PbBi2S4 ternary compound matrix exhibits extremely low lattice thermal conductivity in the full temperature range, and the dependence of lattice thermal conductivity on temperature is not sensitive, which indicates the intrinsic characteristics of the PbBi2S4 ternary compound phonon glass. In this paper, the source of low thermal conductivity of PbBi2S4 ternary compound matrix is analyzed from the crystal structure: PbBi2S4 ternary compound as a member of the same homologous series of galena bismuth mine, its crystal structure is Pnma ; broken NaCl type and Bi2S3 type strip structure leads to the complex layered crystal structure of the compound; and PbBi2S4 has a unique bonding structure with covalent bond and ionic bond coexisting, which will cause uneven chemical environment under the condition of multiple type bonding. In summary, these complex comprehensive results are easy to induce strong lattice anharmonicity, and significantly enhance phonon scattering, so that PbBi2S4 ternary compound matrix has extremely low intrinsic lattice thermal conductivity.

[0037] The thermoelectric properties of examples 1-3 and PbBi2S4 matrix are tested by using the Seebeck and resistivity test system and laser thermal conductivity instrument, including: electrical conductivity σ , Seebeck coefficient S and thermal diffusion coefficient D ( according to the formula PF = σS 2 The power factor can be calculated; according to κ tot = ρC p D The total thermal conductivity can be calculated according to κ lat = κ tot - κ ele The lattice thermal conductivity can be calculated, where κ ele is the electronic thermal conductivity; and according to ZT = S 2 σT / κ tot The final dimensionless thermoelectric merit value, i.e. ZT value) can be calculated, and the results are shown in Figure 4 , and the temperature range of the material is: room temperature to 500 ℃ (300-773 K).

[0038] Figure 4 The thermoelectric performance of examples and PbBi2S4 matrix is shown in the figure. Among them, (a) is the electrical conductivity σ , as can be seen from the figure, the composite InSb can make the electrical conductivity σThe absolute value of the Seebeck coefficient of the PbBi2S4 matrix is reduced slightly by the composite InSb. S As can be seen from the figure, the composite InSb reduces the absolute value of the Seebeck coefficient of the PbBi2S4 matrix slightly. S (c) is the power factor as a function of temperature PF As can be seen from the figure, the composite InSb significantly improves the power factor of the PbBi2S4 matrix PF According to the formula of the power factor, PF = S 2 σ, It can be known that the power factor PF is proportional to the conductivity σ and the Seebeck coefficient S , therefore, the improvement of the power factor PF benefits from the significant improvement of the conductivity σ (d) is the carrier concentration and mobility at room temperature, as can be seen from the figure, the composite InSb significantly optimizes the carrier concentration μ with the mobility of the PbBi2S4 matrix remaining basically unchanged n According to the formula of the conductivity: σ = neμ It can be known that the conductivity σ is proportional to the carrier concentration n and the mobility μ , therefore, the composite InSb can effectively optimize the carrier concentration of the PbBi2S4 matrix n and provide a fast transmission channel for the carriers. (e) is the total thermal conductivity as a function of temperature κ tot and the lattice thermal conductivity κ lat As can be seen from the figure, the InSb composite can further reduce the lattice thermal conductivity of the PbBi2S4 matrix, and the lattice thermal conductivity in the full temperature range (300-773 K) can be reduced from 0.57-0.41 W m -1 K -1 of the PbBi2S4 matrix to 0.56-0.30 W m -1 K -1 of the PbBi2S4-2.5%InSb. (f) is the dimensionless thermoelectric figure of merit ZT value. As can be seen from the figure, a maximum ZT value of 0.72 is achieved in the PbBi2S4-2.5%InSb.

[0039] Figure 5 The lattice thermal conductivity and ZTComparison of values. (a) is the comparison of lattice thermal conductivity, (b) is the comparison of figure ZT Comparison of values. It can be seen from the figure that the InSb composite of the application not only further reduces the lattice thermal conductivity, maintains the advantage of low thermal conductivity of the original matrix, but also effectively improves the electrical transport performance by increasing the carrier concentration while maintaining the basic unchanged mobility after the InSb material is compounded. Finally, the optimization of the thermoelectric performance of PbBi2S4 is realized.

[0040] It can be seen from the above examples that the S-based ternary compound of the application does not contain Te element, exhibits low manufacturing cost; the preparation period is only 30 hours, the process is simple and has high repeatability, and can be manufactured on a large scale; the lattice thermal conductivity of the prepared Pb-Bi-S-based ternary compound PbBi2S4-x%InSb can be as low as 0.56-0.30 W m -1 K -1 ; the maximum thermoelectric figure of merit of the S-based ternary compound can be optimized to 0.72; it has performance and cost advantages, and is a new type of low-thermal-conductivity thermoelectric candidate material with great potential.

Claims

1. A low thermal conductivity Pb-Bi-S-based ternary compound, characterized in that: The chemical formula is: PbBi2S4-x%InSb; where 0.5≤x≤4.0; by compositing InSb into the intrinsically low thermal conductivity PbBi2S4 ternary compound, the electrical transport performance is enhanced while further reducing the lattice thermal conductivity of PbBi2S4, ultimately improving its thermoelectric figure of merit (…). ZT The value has been improved.

2. The low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 1, characterized in that: The molar ratio of Pb, Bi, and S elements in the Pb-Bi-S-based ternary compound matrix is ​​1:2:4, meaning the matrix is ​​a PbBi2S4 ternary compound.

3. The low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 1, characterized in that: The condition is 0.5 ≤ x ≤ 4.

0.

4. The low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 1, characterized in that, The chemical formula of the low thermal conductivity Pb-Bi-S-based ternary compound is: PbBi2S4-2.5%InSb.

5. The method for preparing the low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 1, characterized in that, Includes the following steps: Step 1: Weigh Pb, S, and Bi with independent elemental purity greater than 99.999%, and In and Sb with purity greater than 99.99% according to the atomic stoichiometric ratio of PbBi2S4-x%InSb to obtain a mixture. Step 2: Place the raw materials prepared in Step 1 into a quartz tube, evacuate it, seal it with a flame, and then keep it at a high temperature of 1100±50℃ for more than 6 hours to carry out the melting reaction. Then cool it to room temperature with the furnace to obtain a Pb-Bi-S based ternary compound ingot. Step 3: Grind the Pb-Bi-S based ternary compound ingot into powder, put it into a mold and perform vacuum hot pressing sintering to obtain a dense, low thermal conductivity Pb-Bi-S based ternary compound disc sample.

6. The method for preparing the low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 5, characterized in that, In step 2, the vacuum level inside the quartz tube is less than 10. -3 Pa.

7. The method for preparing the low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 5, characterized in that, In step 2, the temperature control procedure for the melting reaction is as follows: the temperature is raised to 1100±50 ℃ within 15-30 h, and held at that temperature for at least 6 h, and then cooled to room temperature with the furnace.

8. The method for preparing the low thermal conductivity Pb-Bi-S-based ternary compound as described in claim 5, characterized in that, In step 3, the vacuum hot pressing sintering process specifically involves maintaining a pressure of 40-50 MPa and a temperature of 500±50 ℃ for at least 5 minutes.